PELAKSANAAN PATEN OLEH UNIVERSITAS TRISAKTI SEBAGAI PEMEGANG PATEN BERDASARKAN UU NOMOR 13 TAHUN 2016 TENTANG PATEN: Implementation of Patents by Trisakti University as a Patent Holder Based on Law 13 of 2016 on Patents - Grace; Rr. Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2025)
All Patent Rights Holders have obligations that must be carried out, namely paying annual patent maintenance fees and implementing the patents they own, as written in article 20 and article 132 of Law Number 13 of 2016 paragraph (1) letter (e).  If it is violated, the result is that the patent can be invalidated based on a court decision, then how is the implementation of Trisakti University's patent in accordance with Law of the Republic of Indonesia No. 13 of 2016 concerning Patents? This article's research type uses descriptive normative legal research, using secondary and primary data with interviews with IPR Consultants, DJKI staff, Patent Inventors at Trisakti University, as well as interviews with staff at the Research and Innovation Institute of Muhammadiyah University, Surakarta. Data was collected through literature study which was analyzed using qualitative methods, by drawing conclusions deductively. The results of the discussion and conclusions of this article show that not much effort has been made to implement patents by Trisakti University as the patent holder. One of the obstacles is that patent implementation has not yet become a work program at universities, there is a lack of funds and facilities to be able to implement patents, and many inventors do not yet understand their obligations after a patent is granted.